2019
DOI: 10.1002/alr.22438
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic extracts ameliorate nasal allergy by inducing interleukin‐35‒producing dendritic cells in mice

Abstract: Background:The therapeutic efficacy of allergic rhinitis (AR) needs to be improved. Probiotics have immunoregulatory functions. In this study we evaluated the effects of protein extracts of probiotics in the amelioration of AR.Methods: Extracts of Bifidobacterium infantis (EBI) were prepared by lysing the live probiotics. AR mice were developed to be used to evaluate the therapeutic efficacy of EBI. Results:The results show that EBI induced interleukin (IL)-10-producing dendritic cells (DCs) via increasing IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Secreted by CD4 + FoxP3 + Treg cells, IL-35 plays a central role in AR. IL-35 has a well-defined inhibitory function on AR symptomology [ 46 ], indeed serum IL-35 levels are inversely correlated with the total nasal symptom score (TNSS) in children with AR [ 47 ], and recombinant IL-35 has been used successfully as an exploratory therapeutic in an OVA mouse AR model [ 48 ]. Our results align well with these data in that serum and tissue IL-35 levels are inversely correlated to sneezing, goblet cell infiltration of nasal mucosa, and inflammatory cytokine release resulting from AR.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted by CD4 + FoxP3 + Treg cells, IL-35 plays a central role in AR. IL-35 has a well-defined inhibitory function on AR symptomology [ 46 ], indeed serum IL-35 levels are inversely correlated with the total nasal symptom score (TNSS) in children with AR [ 47 ], and recombinant IL-35 has been used successfully as an exploratory therapeutic in an OVA mouse AR model [ 48 ]. Our results align well with these data in that serum and tissue IL-35 levels are inversely correlated to sneezing, goblet cell infiltration of nasal mucosa, and inflammatory cytokine release resulting from AR.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted by CD4 + FoxP3 + Treg cells, IL-35 plays a central role in AR. IL-35 has a well-de ned inhibitory function on AR symptomology 46 , indeed serum IL-35 levels are inversely correlated with the Total Nasal Symptom Score (TNSS) in children with AR 47 , and recombinant IL-35 has been used successfully as an exploratory therapeutic in an OVA mouse AR model 48 . Our results align well with these data in that serum and tissue IL-35 levels are inversely correlated to sneezing, goblet cell in ltration of nasal mucosa, and in ammatory cytokine release resulting from AR.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that IL-35 has the potential to induce autologous Breg cells as well as the treatment of autoimmune and inflammatory diseases (18,19). More studies have demonstrated that IL-10-producing dendritic cells induced by IL-35 and phosphorylating STAT3 can induce immunosuppressive property of IL-10-producing B cells (20).…”
Section: Inflammatory Microenvironmentmentioning
confidence: 99%